Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 35. Beitrag. Mecoptera. - Bartoš, Emanuel (Contributions to Entomology = Beiträge zur Entomologie, 1965)
The author gives the results of his investigations on the Mecoptera of Albania. The material collected in the expedition to Albania by Deutsches Entomologisches Institut contained 11 specimens of Mecoptera belonging to 3 species. One of these is new to the fauna of Albania, which brings the total number of species known from Albania to 4 species.